CerAMfacturing: development of ceramic and multi material components by additive manufacturing methods for personalized medical products. Issue 1 (January 2018) - Scheithauer, Uwe; Johne, Robert; Weingarten, Steven; Schwarzer, Eric; Abel, Johannes; Müller-Köhn, Axel; Günther, Anne; Moritz, Tassilo
Additive manufacturing technologies offer the possibility of tool-free production of components with extremely complex geometry that cannot be attained by any other shaping technique. In our project we are developing a completely new approach for ceramic multi-material additive manufacturing that will allow series production of customized and multifunctional components for manifold applications. In several case studies demonstrators for personalized medical products – micro surgical tools, implants, and remedies – will be manufactured starting with the patient-specific physical dimensions and ending with components validated under practically relevant conditions.